THE EFFECT OF APPLICATION A MODIFIED T-MODEL PLATE ON GD2JPP LEVELS AND AVERAGE GLYCEMIC LOAD OF DMT2 PATIENTS MENU - Mabas, N. Sahila Sukma W. P.; Dwipajati, Dwipajati; Widajati, Endang (Jurnal Gizi dan Pangan Soedirman, 2025)
Background: Type 2 Diabetes Mellitus (DM) is a metabolic disease with a high prevalence in Indonesia. Its management emphasizes TNM using the "T-shaped plate" concept as a modification of the 3J principle . Although the effectiveness of a similar portion approach has been shown globally, there has been no specific study in Indonesia that analyzes the effect of the T-shaped plate concept on levels 2HBP and the average daily glycemic load of the menu in patients with Type 2 DM. Objective: This study aims to analyze the effect of using a T-shaped plate on 2HBP and the average daily glycemic load of the menu in patients with Type 2 DM. Method: This study uses a quantitative method with a pre-test post-test control group design, involving two groups, namely treatment and control for one month of intervention. Using paired t-test statistical test Results Type 2 DM patients are elderly (60-74 years), female, elementary school graduates, with cardiovascular disorders, DM <5 years, and regularly taking medication. There is an increase in energy, carbohydrate, and fiber intake, as well as changes in the type of food ingredients and the accuracy of meal schedules. The results showed no significant effect of the modified T-plate on GD2JPP levels in type 2 diabetes patients. The statistical test result for the control group was 0.66 (>0.05), while for the treatment group, the p-value was 0.07 (<0.05). A significant effect was found in the treatment group with a p-value of 0.00 (<0.05). However, there was no significant effect in the control group with a p-value of 0.25 (>0.05). Conclusion: the results show that the use of T-shaped plates is not significantly related to GD2JPP levels but is significantly related to the average daily glycemic load.